The RHOMOLO impact assessment of the 2014-2020 cohesion policy in the EU regions - Francesca Crucitti; Nicholas-Joseph Lazarou; Philippe Monfort; Simone Salotti (European Commission, Joint Research Centre (JRC), 2022)
We assess the macroeconomic impact of the EU cohesion policy investments deployed during the 2014-2020 programming period, employing updated data on planned expenditures, which in most Member States will take place until 2023. We use the spatial dynamic general equilibrium RHOMOLO in order to quantify the direct and indirect effects of the policy investments in the NUTS 2 regions of the EU within a 20-year time frame. The results suggest that the impact of the policy is sizeable, especially in the less developed regions of the EU. Accordingly, regional disparities are shown to decrease thanks to the policy intervention. The policy also has a positive impact at the EU level, GDP in the EU being 0.4% higher in 2021 compared to a scenario without cohesion policy.
Keywords: C68; R13; 330; policy; regional growth; regional development; general equilibrium modelling